The Effect of Product Quality and Service on Customer Satisfaction with Goodluch Products - Alviana Cahara Setiadi; Cicie Prilianti (Takaza Innovatix Labs Ltd., 2026)
This study examines the influence of product quality and service quality on customer satisfaction with Goodluch, a local digital-based fashion brand. The research aims to determine the extent to which these two variables—product quality (X₁) and service quality (X₂)—affect consumer satisfaction (Y). A descriptive-verificative quantitative method was used with 96 respondents selected through simple random sampling. Data were collected using questionnaires and documentation, then analyzed using multiple linear regression with SPSS. The results show that product quality (sig. = 0.057 > 0.05) has no significant effect on customer satisfaction, while service quality (sig. = 0.013 < 0.05) has a significant positive effect. Simultaneous testing (F = 6.045; sig. = 0.003) indicates that both factors jointly affect satisfaction. The study concludes that Goodluch customer satisfaction is predominantly influenced by service quality supported by adequate product quality. Improving service responsiveness and product consistency is recommended to enhance loyalty.